Analisis Manajemen Perubahan terhadap Pemberdayaan Pertumbuhan UMKM dan Ekonomi Umat Islam di Kota Medan - Rabiatun Adawiyah; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research was to find out changes in economic growth in the city of Medan. While the benefits of this research are as initial information to determine changes in the economic development of SMEs and the Muslim economy in the city of Medan. This research is to analyze economic growth in Medan City in the MSME cooperative sector and the Muslim economy as an effort to overcome the 2023 economic crisis which is a Medan City government policy. This research was carried out by means of a literature study or library research. Data collection used the library research method. The results of the research are that the government of Medan City adopted a policy of increasing MSMEs and the Muslim economy in the city of Medan, and the growth of MSMEs and the Muslim economy in Medan City has advanced and the number is very large, so that it has a very good influence in advancing economic growth.